A collaborative approach to harmonizing online and offline activities for teenagers in the era of digital technology - Zeng Zekun,; Osipenko E.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create and theoretically support a synergistic framework for the equilibrium between virtual and physical activities in adolescents aged 12 to 18 in the context of the digital transformation of society. Methods and structure of the study. Based on the examination of WHO data and the pilot implementation in a sports school (with a sample size of 60), a framework is suggested that encompasses five functional components: educational-methodological, motivational-stimulating, regulatory-infrastructural, diagnostic-adaptive, and socio-cultural. The framework is put into practice through educational initiatives, gamification, digital monitoring systems, and cultural practices. The study employs methods such as literature review, questionnaire surveys, and qualitative data analysis. Results and conclusions. The preliminary findings of the model evaluation revealed a decrease in screen time of 15-20% and an increase in physical activity of 20-30%. The key principles of operation are a positive feedback loop, dynamic activity planning, and content symmetry. A positive feedback loop fosters motivation by linking digital and physical accomplishments. Dynamic planning personalizes the activity schedule, considering biorhythms, academic workload, and seasonal factors. Content Symmetry offers exercise programs that mirror the time spent on digital devices. The model encourages the development of sustainable motivation for a healthy lifestyle, reducing the risks of physical inactivity and digital exhaustion. The model is still undergoing testing, which will enable us to refine its effectiveness on a larger scale.